Determinants of food security in Tanzania: gendered dimensions of household headship and control of resources - Mason, R.F.; Ndlovu, P.; Parkins, J.R.; Luckert, M.K. (Springer, 2015)
This paper examines heterogeneous impacts of gendered household headship and control of resources on food security in rural Tanzania (as measured by a World Food Programme score based on quantity and quality of food consumed in the household over a 7 day period). Analysis with minimal attention to heterogeneity in gender considerations indicates no differences in household food security between male and female-headed households. But with a more differentiated household headship variable (reflecting heterogeneity in household composition) and accounting for gendered differences in resource ownership, the results differ markedly. Using more gender-disaggregated variables, our results show significant differences between female-headed and male-headed households. In these results we find support for the claim that gender norms in the study villages often restrict women’s access to resources, resulting in more vulnerable female-headed households. Female-headed households with no male adults present are particularly vulnerable. The study also points to specific opportunities for enhanced food security with attention to female and joint ownership of livestock. These results represent a hopeful sign that efforts to enhance female livestock ownership could be a useful strategy to address lower levels of food consumption in these Tanzanian villages.